Meningkatkan Hasil Belajar Siswa Melalui Metode Make A Match Pada Pembelajaran PAI di SDIT An Nahl - Fitri Nefrita; Roza Elfira; Ria Kemala Sari; Yulia Ningsih; Fadhilla Yusri; Adi Warman (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study is Classroom Action Research (CAR). The goal is to use the Make a Match learning model to enhance students' learning outcomes in the Islamic Education course for Grade IV students at SDIT An Nahl. The research was conducted in the An Nur class with a total of 20 female students. The fact that certain students had not yet achieved the passing requirements in the Islamic Education and Character Education courses served as the impetus for the study. Students' engagement was low because the learning process was still dominated by teacher-centered lectures. Low student interest and enthusiasm for learning resulted in less-than-ideal learning outcomes. The researcher used the Make a Match method to teach the Noble Examples of Asmaul Husna. Make a Match technique are to boost student interest in the learning process and create a more dynamic learning environment because students were actively participating in the process. Students' interactions with teachers and with each other improved, promoting cooperation and communication skills. The learning objectives of the students were also positively impacted by this